THE MODERATING EFFECT OF INSTITUTIONAL QUALITY ON CORPORATE GOVERNANCE AND FINANCIAL STATEMENT FRAUD IN AN EMERGING ECONOMY - Inu Imoudu Sule; Henry Emife Monye-Emina (Oradea Journal of Business and Economics, 2022)
The study examines corporate governance and financial statement fraud: the moderating role of institutional quality. The study adopted the ex-post facto research design and a sample of 75 non-financial firms listed on the Nigerian Exchange Group (NGX) was used for the study. The binary regression technique was adopted. The results reveal that, board size has shown a positive effect on Financial Statement Fraud. Board independence is negative both in the response and selection equations. Foreign Ownership is negative both in the response and selection equation and significant, and Finally, the study recommends that listed firms may need to cut down their board sizes. Although there is still no consensus on what an optimal board size should be, the study is of the opinion that firms with board sizes above the industry average should look at bringing down their board sizes and also corporate boards should increase their board independence levels by bringing in more non-executive directors. On the part of foreign ownership presence in boards, they are indeed diverse in line with the resource-based view theory and this study confirms their effectiveness in constraining financial statement fraud. Hence it is recommended that companies should seek and maintain some level of foreign ownership presence in their boards.